Specific antibodies protect gamma-irradiated mice against Francisella tularensis infection - Kubelkova, Klara; Krocova, Zuzana; Balonova, Lucie; Pejchal, Jaroslav; Stulik, Jiri; Macela, Ales (Microbial pathogenesis, 2012)
The role of antibodies in the course of Francisella tularensis (F. tularensis) infection is still a subject of debate. The understanding of the poorly described role of humoral immunity is more than important for the effort to develop effective prophylactic procedure against the infection with Francisella virulent strains. We utilized the model of gamma-irradiated mice for the studies of the protective role of anti-F. tularensis antibodies in order to partially eliminate cellular responses. The model of gamma-irradiated mice can also demonstrate the responses of immunocompromised host to intracellular bacterial infection. The gamma-irradiation by doses greater than 3 Gy completely impairs the resistance to infection and causes a disbalance of cytokine production in mice. In this study, we demonstrate that passive transfer of immune sera protected irradiated mice against subsequent infection with strains of F. tularensis subsp. holarctica. Naïve mice of BALB/c or C3H/CBi strains were subjected to passive transfer of sera obtained from immunized mice with live vaccine strain (LVS) F. tularensis LVS, F. tularensis subsp. holarctica strain 15, heat-killed F. tularensis LVS, or heat-killed strain 15 two hours before infection with lethal doses of LVS or strain 15. The passive transfer of sera obtained from immunized mice conferred full protection of naïve unirradiated as well as sublethally irradiated mice against low lethal doses of infection with F. tularensis LVS or strain 15, in all variants of the experiments. In addition, the passively protected mice that survived the primary infection with F. tularensis LVS were protected also against further secondary challenge with a highly virulent strain of F. tularensis subsp. tularensis SchuS4. Moreover, the first evidence of combination of successful passive transfer of immunity by specific antisera and subsequent active immunization of immunocompromised animals is demonstrated. In summary, we demonstrate that B cell-mediated effector responses together with the induction of T cell-mediated immunity both play an important role in naïve and also in immunocompromised mice and this fact it would be appropriate to take into the account in the design of new vaccines.
Keywords: analýza přežití; modely nemocí na zvířatech; pasivní imunizace; tularemie; Mice, Inbred C3H; myši inbrední BALB C; myši inbrední C3H; Gamma Rays; Mice, Inbred BALB C; Survival Analysis; Animals; lidé; ženské pohlaví; Humans; zvířata; Tularemia; Immunization, Passive; Disease Models, Animal; myši; protilátky bakteriální; Mice; Female; záření gama; Francisella tularensis; Antibodies, Bacterial